2014
DOI: 10.1093/cid/ciu447
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of Hepatitis C Virus: Systematic Review and Meta-analysis

Abstract: Updated pooled estimates of vertical hepatitis C (HCV) infection risk to children of HCV RNA–positive mothers ranges between 5.8% and 10.8%, depending on maternal HIV coinfection. Additional risk factors need to be captured and reported by future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
394
3
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(423 citation statements)
references
References 41 publications
4
394
3
22
Order By: Relevance
“…Simple distribution Naïve Bayes and decision tree created by Rapid I version 4.6 emphasized the level of maternal HCV-related vertical transmission; > 3× 10 6 IU should be considered as the high level of vertical prediction, reported in our previous work [13] , and CS should be likely an important route of global HCV transmission especially in developing countries [ Figures 1 and 2]. However, the level of maternal viremia is still a matter of scientific debate in such vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple distribution Naïve Bayes and decision tree created by Rapid I version 4.6 emphasized the level of maternal HCV-related vertical transmission; > 3× 10 6 IU should be considered as the high level of vertical prediction, reported in our previous work [13] , and CS should be likely an important route of global HCV transmission especially in developing countries [ Figures 1 and 2]. However, the level of maternal viremia is still a matter of scientific debate in such vertical transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of transmission (one in every 20 children) delivered by chronic HCV-infected women highlights that vertical transmission likely constitutes the primary transmission route among children. These updated estimates are considered as a basis for decision making in prioritization of the research into risk-reducing measures [6][7][8] . Recently, data mining (DM) programming allows clinicians to extract hidden factors that lead to such disease progression or regression in an artificial intelligence manner [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms leading to perinatal HCV transmission are currently not well understood. Likely risk factors include perinatal practices (fetal scalp monitoring and caesarean‐section delivery), extended exposure to maternal blood, high levels of HCV viremia during pregnancy, and co‐infection with human immunodeficiency virus (HIV) 15, 16, 17, 18, 19. Although some studies have challenged several of these assumptions,20, 21 a recent meta‐analysis concluded that maternal HIV co‐infection is the most important determinant of the risk of perinatal transmission 15…”
Section: Epidemiologymentioning
confidence: 99%
“…Results from a recent meta-analysis suggest that the risk of vertical transmission from anti-HCV positive and RNA-positive women is about 5.8% (95% CI, 4.2%-7.8%), and the risk to children born to an anti-HCV positive mother with spontaneous clearance of infection (RNA negative) was insignificant (37,38).…”
Section: Vertical Transmissionmentioning
confidence: 99%